2015
DOI: 10.1039/c5tb00004a
|View full text |Cite
|
Sign up to set email alerts
|

What makes a good graphene-binding peptide? Adsorption of amino acids and peptides at aqueous graphene interfaces

Abstract: Investigation of the non-covalent interaction of biomolecules with aqueous graphene interfaces is a rapidly expanding area. However, reliable exploitation of these interfaces in many applications requires that the links between the sequence and binding of the adsorbed peptide structures be clearly established. Molecular dynamics (MD) simulations can play a key role in elucidating the conformational ensemble of peptides adsorbed at graphene interfaces, helping to elucidate these rules in partnership with experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
122
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 92 publications
(139 citation statements)
references
References 83 publications
13
122
1
Order By: Relevance
“…The water molecules were described with the CHARMM‐modified version of the TIP3P water model . This combination of force‐fields have been previously implemented by Hughes et al to study aqueous graphene/amino acid interfaces . In brief, after consideration and testing of a range of simulation approaches, SAMD was used to model these adlayers.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The water molecules were described with the CHARMM‐modified version of the TIP3P water model . This combination of force‐fields have been previously implemented by Hughes et al to study aqueous graphene/amino acid interfaces . In brief, after consideration and testing of a range of simulation approaches, SAMD was used to model these adlayers.…”
Section: Methodsmentioning
confidence: 99%
“…Alternatively, molecular dynamics (MD) simulations have the potential to address some of these questions, and have demonstrated a complementary route to elucidating the atomic‐scale details required to enable clear interpretation of experimental data relating to surface organization of biomolecules on graphene/graphite . To this end, numerous theoretical studies have reported the adsorption modes and configurations of amino acids on graphene/graphite surfaces using MD simulation …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[27][28][29] Amongt hem, Grimme's dispersion-correction (so called D3) is the most populara bi nitio approacht od ealing with the weak noncovalenti nteractions for whicht he "gold-standard" coupled-cluster CCSD(T) becomes prohibitive. Free-energy techniques have been used to calculate the adsorption affinities of amino acids on model gold, [32][33][34][35] silver, [36] zinc oxide surfaces, [37] and graphenic materials, [38,39] as well as for contaminants on amorphous silica. Alternatively,c lassical molecular dynamics simulations with atomistic models and explicit solvent have arisen as ap romising approach to elucidating interactionsb etween commonn anomaterials and organic molecules.…”
Section: Introductionmentioning
confidence: 91%
“…In this case, there was an abrupt increase in the interaction energy of the arginine residue at about 10 ns, almost doubling its value and exceeding the energy of −80 kJ/mol exhibited by the tryptophan residue. This event was likely to be caused by the rapid structural change in an arginine sidechain as it adsorbed onto graphene within a short period of time, as arginine residues were previously shown to interact strongly with graphene [Hughes et al, 2015]. The conformational difference is highlighted in the insets of Figs.…”
Section: Behaviors Of the Multiple Segments Upon Adsorption Onto The mentioning
confidence: 94%